Solvability of the system of linear inequalities - Vilkas, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. И. Вилкас. Разрешимость системы линейных неравенствE. Vilkas, Tiesinių nelygybių sistemos išsprendžiamumas